Application of Yeast Hydrolysate in Extracellular Lipase Production by Geotrichum candidum in Shaken Flasks, Stirred Tank, and Airlift Reactors. (22nd July 2015) - Maldonado, Rafael Resende; Aguiar‐Oliveira, Elizama; Pozza, Eduardo Luiz; Costa, Fátima Aparecida Almeida; Mazutti, Marcio A.; Maugeri, Franciso; Rodrigues, Maria Isabel
<x xml:space="preserve">Abstract</x> Lipase production by Geotrichum candidum NRRL Y‐552 was studied using an alternative nitrogen source, yeast hydrolysate (Prodex‐lac®), and soybean oil as the carbon source and inducer of lipase production. Factorial design and response surface methodologies were applied to obtain optimized conditions for lipase production in shaken flasks, defined as: 3.5 g/100 mL of yeast hydrolysate and 0.7 g/100 mL of soybean oil with an initial pH of 7.0 at 30 °C and 250 rpm. The resulting lipase activity after 48 h was 24.3 U/mL (0.506 U/mL.h), 52 % higher than with peptone under the same conditions (U = the amount of enzyme required to liberate 1 µmol of fatty acid per minute). Lipase production with the optimized medium was conducted in a stirred tank reactor and in an airlift bioreactor, both at 30 °C and 300 rpm; the best results obtained were 15.4 U/mL after 32 h of fermentation (0.481 U/mL.h) and 19.24 U/mL after 32 h of fermentation (0.601 U/mL.h) at 1 vvm, respectively. The results presented here from both bioreactors showed similar results to a previous study with the same microorganism under the same conditions using peptone as a nitrogen source. In addition, yeast hydrolysate is a cheaper nitrogen source than peptone and yeast extract, which permits a cost reduction above 90 % under similar conditions.